JAMINAN SOSIAL TENAGA KERJA KONTRAK PADA PT.DUTAPALMA NUSANTARA - Maulini, Dhinda Rielna; Lestari, Rika; Hasanah, Ulfia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Labor is the source of foreign exchange for the State of Indonesia, one of its functions is to national development. Development of human resources is one part that is integral to national development. Labor contract, permanent and non-permanent employees have the same rights and obligations, particularly in terms of providing social security. The labor contract workers and casual workers should be given significant protection in both the health insurance and economic security, so as to increase productivity in the place he works. One form of such protection is the Social Security Agency is set in Act No. 24 of 2011 of the Social Security Agency.PT.Dutapalma archipelago is one company that also runs the program. To determine the program implementation BPJS for Labor Contract at. Dutapalma Nusantara, the author intends to do the research. The formulation of the problem, namely: (1) Determine the implementation of Social Security Workers of the labor contract at PT. Dutapalma Nusantara Pekanbaru (2) Knowing the obstacles in the implementation of Social Security Workers of the labor contract at PT. Dutapalma Nusantara Pekanbaru (3) Knowing efforts to overcome obstacles to implementation of Social Security Workers of the labor contract at PT. Dutapalma Nusantara Pekanbaru. The purpose of this research is: (1) To explain how the implementation of social security programs for workers PT.Dutapalma contract archipelago in Pekanbaru (2) To determine the obstacles in the implementation of social security programs for workers PT.Dutapalma contract archipelago in Pekanbaru ( 3) to know the efforts to overcome obstacles in the implementation of social security programs for workers PT.Dutapalma contract archipelago in Pekanbaru.This study took Locations in PT.Dutapalma archipelago in Pekanbaru with the methods used in evaluating and sampling is descriptive method, that describe or depict the full facts of the object studied, analyzed and interpreted in order to be concluded. This research is sociological, materials research conducted by surveying the field to make observations and interview data collection tools, questionnaires, and literature review.From the results of this penelitiaan concluded that the procedure of membership BPJS against labor contract is in accordance with the PT.Dutapalma Nusantara has not been regulated in Law No. 24 of 2011 concerning Social Security Agency. Because in running the program BPJS injustice given by the company to the labor contract. Completion of this problem by registering all workers without any discrimination against contract labor.Keywords: -Contract Labour - Social Security Agency